2006
DOI: 10.1093/jxb/erj111
|View full text |Cite
|
Sign up to set email alerts
|

Root plasma membrane H+-ATPase is involved in the adaptation of soybean to phosphorus starvation

Abstract: The plasma membrane H+-ATPase plays an important role in the plant response to nutrient and environmental stresses. However, the involvement of plant root plasma membrane H+-ATPase in adaptation to phosphate (P) starvation is not yet fully elucidated. In this study, experiments were performed with soybean roots in low-P nutrient solution (10 microM). Treatment with fusicoccin, an activator of the plasma membrane H+-ATPase, increased P uptake by 35%, while vanadate, an inhibitor of plasma membrane H+-ATPase, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 39 publications
2
74
1
1
Order By: Relevance
“…It is also modulated by calcium ions, abscisic acid, auxin, cGMP, light, phospholipids and kinases (Kinoshita et al 1995;Michelet and Boutry 1995;Suwastika and Gehring 1999;Peng et al 2003). Furthermore, the activity and gene expression of this enzyme are affected by various environmental factors, such as phosphorus starvation (Shen et al 2006), Al stress (Ahn et al 2001) and salinity (Vitart et al 2001;Yang et al 2007). An induced PM H ?…”
Section: Introductionmentioning
confidence: 99%
“…It is also modulated by calcium ions, abscisic acid, auxin, cGMP, light, phospholipids and kinases (Kinoshita et al 1995;Michelet and Boutry 1995;Suwastika and Gehring 1999;Peng et al 2003). Furthermore, the activity and gene expression of this enzyme are affected by various environmental factors, such as phosphorus starvation (Shen et al 2006), Al stress (Ahn et al 2001) and salinity (Vitart et al 2001;Yang et al 2007). An induced PM H ?…”
Section: Introductionmentioning
confidence: 99%
“…At 50% flowering stage the ATPase activity at 0% P was 57.48 and 48.9% higher in comparison with 100% P levels ( Table 4). Hong Shen et al, (2006) found that P starvation enhanced the activity of plasma membrane H + -ATPase in soybean roots. The plasma membrane derived from active proteoid roots of P-deficient plants showed a more than two times higher ATPase activity than P-sufficient roots.…”
Section: Adenosine Triphosphatase (Atpase) Activitymentioning
confidence: 99%
“…In acidified growth medium, suitable for fungal growth, yeast cells challenged with the herbicide 2,4-D suffer a strong reduction in their cytosolic and vacuolar pH Simões et al, 2003), which is counteracted by the activation of the plasma and vacuolar membrane H + -ATPases Teixeira et al, 2005). Significantly, auxins were also shown to induce the activity of the Arabidopsis plasma membrane H + -ATPase, contributing to maintain the intracellular pH in plant roots (Shen et al, 2006). Based on the participation of the MDR transporters Tpo1p and Pdr5p (belonging to the MFS and ABC superfamily, respectively) in yeast resistance to 2,4-D, the active export of the 2,4-D counter-ion catalysed by these plasma membrane transporters was postulated (Teixeira & Sá-Correia, 2002).…”
Section: Mfs-mdr Transportersmentioning
confidence: 99%